Sigmoid colon perforation due to geophagia - Ilhan, Y; Çifter, C; Dogru, O; Akkus, MA (Assoc Soc Scientifique Med Belges, 1999)
Geophagia can be a problem in mentally handicapped patients. This case report presents a 71-year-old mentally handicapped women who had to be operated in emergency for colonic perforation due to geophagia.
Keywords: geophagia; colon; perforation